Insights Into the Somatic Mutation Burden of Hepatoblastomas From Brazilian Patients - Aguiar, Talita Ferreira Marques; Rivas, Maria Prates; Costa, Silvia; Maschietto, Mariana; Rodrigues, Tatiane; Sobral de Barros, Juliana; Barbosa, Anne Caroline; Valieris, Renan; Fernandes, Gustavo R.; Bertola, Debora R.; Cypriano, Monica; Caminada de Toledo, Silvia Regina; et al. (Frontiers in Oncology, 2020)
Hepatoblastoma is a very rare embryonal liver cancer supposed to arise from the impairment of hepatocyte differentiation during embryogenesis. In this study, we investigated by exome sequencing the burden of somatic mutations in a cohort of 10 hepatoblastomas, including a congenital case. Our data disclosed a low mutational background and pointed out to a novel set of candidate genes for HB biology, which were shown to impact gene expression levels. Only three recurrently mutated genes were detected: CTNNB1 and two novel candidates, CX3CL1 and CEP164. A relevant finding was the identification of a recurrent mutation (A235G) in two hepatoblastomas at the CX3CL1 gene; evaluation of RNA and protein expression revealed up-regulation of CX3CL1 in tumors. The analysis was replicated in two independents cohorts, substantiating that an activation of the CX3CL1/CX3CR1 pathway occurs in hepatoblastomas. In inflammatory regions of hepatoblastomas, CX3CL1/CX3CR1 were not detected in the infiltrated lymphocytes, in which they should be expressed in normal conditions, whereas necrotic regions exhibited negative labelling in tumor cells, but strongly positive infiltrated lymphocytes. Altogether, these data suggested that CX3CL1/CX3CR1 upregulation may be a common feature of hepatoblastomas, potentially related to chemotherapy response and progression. In addition, three mutational signatures were identified in hepatoblastomas, two of them with predominance of either the COSMIC signatures 1 and 6, found in all cancer types, or the COSMIC signature 29, mostly related to tobacco chewing habit; a third novel mutational signature presented an unspecific pattern with an increase of C>A mutations. Overall, we present here novel candidate genes for hepatoblastoma, with evidence that CX3CL1/CX3CR1 chemokine signaling pathway is likely involved with progression, besides reporting specific mutational signatures.